Mediating role of trust and privacy concerns between web assurance mechanism and purchase intention of online products - Charu Saxena; Pratibha Thakur (Telematics and Informatics Reports)
Trust and privacy concerns are the rudimentary pillars of all the crucial online transactions. Web assurance mechanisms such as secure payment gateways, trust seals, and data protection measures, are designed to build credibility between consumers and online businesses. This research study attempts to examine the mediating role of trust and privacy concerns between web assurance mechanisms and purchase intention of online products. This will provide valuable insights to the underlying psychological processes and factors that influence consumer behavior in the online shopping context. A conceptual model has been framed to investigate the direct and indirect relationship between web assurance mechanism and purchase intention of online products via trust and privacy concern. This study uses data collected from 342 respondents. Smart PLS4 was used for the assessment of measurement model and structural model. The research findings claims that the web assurance mechanism has a significant impact on purchase intentions, privacy concerns, and trust. It was also found that when privacy concerns and trust were introduced as mediators, the indirect effect was still significant, which indicates that privacy concerns and trust partially mediate the direct relationships. The findings of the study can help identify the specific factors that contribute to consumer comprehension and assess how web assurance mechanisms influence these concerns. The findings can inform the development of privacy-enhancing measures and policies to alleviate consumer worries and increase purchase intention.